Marshall Properties and Rutting Resistance for Asphaltic Mixtures Modified by Nano-Montmorillonite (Journal of Engineering, 2025)
Rutting is a significant problem in flexible asphalt pavements, causing permanent deformation. Increased traffic, axle load, tire pressure, and hot weather have recently accelerated rutting in flexible pavements. Several researchers have suggested using nanomaterials to improve asphalt pavement and prolong its lifespan. The nano clay chosen for this study is a natural, hydrophilic montmorillonite in its raw form. Consequently, incorporating Nano-montmorillonite (MMT) into asphalt mixtures to improve performance under dynamic loads has gained significant attention. This can help reduce rutting damage and ensure the safety and durability of road surfaces. This study examines the impact of incorporating MMT into hot mix asphalt on the Marshall properties and resistance to rutting. It involved determining the optimal asphalt content using the Marshall design method, as well as the rutting depth for asphalt mixes using wheel tracking tests, for mixtures comprising different MMT percentages (2%, 4%, and 6%) as a percentage of the asphalt binder. The optimal asphalt content was 4.93% for the control mix. The inclusion of 6% MMT increased the Marshall stability the most by 16.79%. Marshall flow decreased when MMT was added. The control mix had a Marshall flow of 3.30 mm, but when using 4% MMT, the flow decreased to 2.81 mm, the most significant reduction. The ideal proportion of MMT was 6%, resulting in a 39.79% reduction in rut depth compared to the control mixture.